STUDY OF MICROBUBBLE FOR ELECTROCHEMICAL REDUCTION OF CO2 TO FORMIC ACID - Angkasa, Albert
CO2 accumulation in the atmosphere has caused global temperature rise and the phenomenon of global warming. Therefore, the atmospheric concentration of CO2 must be minimized to alleviate the effect of global warming. Currently, several technologies such as carbon capture and storage (CCS), CO2-enhanced oil recovery (EOR), and coal bed methane recovery (CBM) have been developed in order to abate CO2 emission from fossil fuel combustion. Thus, this experiment is intended to reduce CO2 electrochemically to produce formic acid which is highly used as a feedstock in many chemical processes. In this research, electroreduction of CO2 gas was carried out using Pb-Sn cathode, Pt-Ir anode, KHCO3 catholyte, and diluted H2SO4 anolyte. CO2 gas was dissolved in catholyte by means of microbubbling. The bubble size and the electrode geometry were used as variables of this experiment. The produced formic acid was analyzed with fouriertransform infrared spectroscopy (FTIR). The cathode was examined with scanning electrode microscope (SEM-EDX), preceding and following the electrolysis. The FTIR characterisation shows that CO2 electrolysis produces formic acid. Data of electrolysis current displays that microbubble usage theoretically produces 45,3% more formic acid than millibubble usage. Usage of cathode with the diameter of 0,5 cathode chamber diameter theoretically produces 26,3% more formic acid, compared to usage of cathode with the diameter of 0,25 cathode chamber diameter. Furthermore, the data log of the electric current to time displays that the current declines over time due to the formation of oxide layer on the cathode.